Developing Institutional Arrangements for Sustainable Development within Mineral Rich Resource Countries: the Case of Mongolia - Burmaa, Natsag; Baasanjav, Ganbaatar (Geomatics and Environmental Engineering, 2021)
A primary goal of the article is to explore the theoretical understanding among scholars about how institutional arrangements for sustainable local development partnerships in mineral resource‑rich countries are created. A success factor for implementing sustainable development goals (SDGs) is creating a prop‑ er institutional arrangement. Interviews and questionnaires, a mixed research method, were completed with officials and citizens from selected provinces. We reached to the following results: among others there is a weak understanding of partnership‑related local community development among stakeholders. Therefore, long term strategic planning and management which involves all parties in the decision‑making process should be created. In addition, building both horizontal and vertical institutional arrangements that provide for the participation of related stakeholders is an essential element for building successful and sustainable local development partnerships.